An agonist of the CXCR4 receptor accelerates the recovery from the peripheral neuroparalysis induced by Taipan snake envenomation - Stazi, Marco; D’Este, Giorgia; Mattarei, Andrea; Negro, Samuele; Lista, Florigio; Rigoni, Michela; Megighian, Aram; Montecucco, Cesare (PLOS Neglected Tropical Diseases, 2020)
Author summary We have taken here a different angle in the search for novel treatments of snake envenomings by focusing of the phase of recovery from the peripheral neuroparalysis caused by neurotoxic snakes. This is a critical period that may require mechanical ventilation and prolonged hospitalization. We have found a drug, dubbed NUCC-390, which accelerates the functional recovery from peripheral neuroparalysis caused by the Taipan venom in mice, by acting on the CXCR4 receptor. In fact, we found here that this receptor is expressed by the motor neuron at the site of damage that, in the case of many snake venoms containing presynaptic PLA2 neurotoxins, consists in the degeneration of the axon terminal. NUCC-390 binds to CXCR4 and acts similarly to its natural agonist the chemokine CXCL12α. The compound is not toxic and can be administered after the snakebite and therefore it has the potential of becoming a non-expensive addition to the currently available antisera treatment whose efficacy is limited by the need of delivery shortly after snakebite.